2021
DOI: 10.3390/foods10030545
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of a Novel Microwave-Assisted Induction Heating (MAIH) System on White Shrimp Cooking

Abstract: The microwave-assisted induction heating (MAIH) system provides comprehensive heating by combining microwave heating (with 1300 W of power and 2450 MHz of frequency) in the top part and induction heating (with 1800 W of power) in the bottom part. In this study, fresh white shrimps were placed in a sealed crystallized polyethylene terephthalate (CPET) container and heated in the MAIH system at two temperatures (130 and 90 °C) from 60 to 120 s. Afterwards, the shrimp samples were rapidly cooled, and the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…APC and PBC are both important indexes for evaluating the quality of fresh and low-temperature-stored aquatic products. A similar finding was previously demonstrated by Lee et al [11], who found that MAIH at 130 • C for 80 s or 90 • C for 100 s significantly reduced the APC level of white shrimp to become negligible (<2.0 log CFU/g). Regarding the HBC and coliform counts, the raw hard clam had an initial HBC of 3.95 log CFU/g and an initial coliform of 2.72 log CFU/g (Table 2).…”
Section: Microbial Count Determination Of Hard Clamsupporting
confidence: 90%
See 1 more Smart Citation
“…APC and PBC are both important indexes for evaluating the quality of fresh and low-temperature-stored aquatic products. A similar finding was previously demonstrated by Lee et al [11], who found that MAIH at 130 • C for 80 s or 90 • C for 100 s significantly reduced the APC level of white shrimp to become negligible (<2.0 log CFU/g). Regarding the HBC and coliform counts, the raw hard clam had an initial HBC of 3.95 log CFU/g and an initial coliform of 2.72 log CFU/g (Table 2).…”
Section: Microbial Count Determination Of Hard Clamsupporting
confidence: 90%
“…The rigid induction half-cavity formed between the top half microwave heating cap and bottom half induction base prevents expansion of the packaged foods when heated above 100 • C, thereby eliminating the need for overpressure, which is commonly produced by pressurized steam or water in conventional canning systems [10]. Recently, MAIH has been used for the cooking and pasteurization of shrimp for the first time in our research group [11]. Additionally, a previous piece of research also reported that after shrimps were processed by MAIH heating, the temperatures of all samples in the CPET container were within the range of 90-100 • C, as measured by thermal images; the uniform temperature distribution indicated that these heated shrimps underwent uniform heating [12].…”
Section: Introductionmentioning
confidence: 99%
“…Under the heating condition of 90 • C, the first stage was maintained for 100 s, and in the second stage, processing time ranged from 10 to 50 s with increments of 10 s each (Table 1). The heating time design of this scaled-up MAIH study mainly refers to our previous research on experimental MAIH [13]. Our previous study demonstrated that the optimal cooking condition of white shrimp can be achieved by experimental MAIH at 130 • C for 80 s or 90 • C for 100 s [13].…”
Section: Scaled-up Maih Processingmentioning
confidence: 99%
“…The heating time design of this scaled-up MAIH study mainly refers to our previous research on experimental MAIH [13]. Our previous study demonstrated that the optimal cooking condition of white shrimp can be achieved by experimental MAIH at 130 • C for 80 s or 90 • C for 100 s [13]. Therefore, in order to reduce the number of repeated heating conditions, the first stage heating time was set to 80 s at 130 • C and 100 s at 90 • C; the second stage heating time (holding time) only gradually increased to determine whether the white shrimp was fully cooked.…”
Section: Scaled-up Maih Processingmentioning
confidence: 99%
See 1 more Smart Citation